Effects of Amount and Type of Self-Regulation Opportunity during Skill Acquisition on Motor Learning - Jones, Andrea (My University, 2010)
This study examined the effects of varying levels and type of self-control on the acquisition and retention of a motor task. Four sequence timing tasks were used, each with their own sequence order and target time. The goal of the task was to complete the sequence with a movement time as close to the target time as possible. An experimental group was given self-control over the practice variable of task ordering as well as constrained self-control over feedback scheduling. Three control groups were yoked to certain aspects of the experimental group. Control group A was yoked to the task order decisions made by the experimental group but permitted to self-control their feedback schedule. Control group B was yoked to the experimental group's chosen feedback schedule but permitted to control their trial order. The last control group, C, was yoked to both the feedback and task order schedule of the experimental group. Groups that selfcontrolled their own feedback schedules; the experimental group and control group A, were slower to demonstrate decreases in absolute constant error at the beginning of acquisition. Throughout acquisition, these same groups were able to utilize the feedback requested after a given trial to significantly improve performance on the following trial of the same sequence type. During acquisition, and retention, the self-controlled feedback groups had average movement times that were more accurate to the average target time than did other groups. No further differences between groups were found during retention or transfer. These results suggest that the self-controlled conditions used in this study affect performance during acquisition but do not necessarily enhance the amount of information retained in the long term.
Keywords: Kinesiology; Kinesiology